Service quality of public transportation : a case study on passenger satisfaction toward mini bus service in Kota Kinabalu / Shaierah Gulabdin and Mardianie Danil - Gulabdin, Shaierah; Danil, Mardianie (2015)
Mini bus was one of the vehicles used by the individual to arrive safely go to one location to another. Various factors to the selection of vehicles used to go from one location to another location, it includes to the attitude of the driver, the situation inside and outside the bus whether handled or not handled properly. A studies on factors that encourage individuals to minibus selection as the main vehicle to get to a location that has been done by selecting Kota Kinabalu as a location study, it is involving five dimensions of service quality that is reliable, responsiveness, assurance, empathy, and tangible. This paper aims to investigate five dimensions of quality of the services listed, the analysis carried out by analysing the main factors toward individual satisfaction in choosing a mini bus vehicles with reference to the five dimensions of service quality are listed. This research is using quantitative methods with a questionnaire to collect data from passengers in Kota Kinabalu.